2021
DOI: 10.1088/2053-1591/abf6fa
|View full text |Cite
|
Sign up to set email alerts
|

Study of methionine as green corrosion inhibitor for TWIP steel in neutral chloride solution

Abstract: The influence of Methionine (MTI) on corrosion behavior of Twinning induced plastic (TWIP) steel in 3.5wt.% NaCl solutions was investigated using electrochemical techniques, scanning electron microscopy (SEM), white light interferometer (WLI) analyses and Raman spectra. With increasing inhibitor concentration, the corrosion inhibition rate first increased and then decreased, and the maximum inhibitor efficiency was found to be 30 mg l−1 MTI. MTI was acting as a mixed-type inhibitor. The inhibition effect of MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Based on the electrochemical results, the similar electrochemical behaviors at 298 and 308 K are observed for the corrosion inhibition performance of Q235 steel as incorporation of FH inhibitor; thus, the electrochemical test results of Q235 steel at 298 K are selected to conduct the subsequent characterizations, such as Raman, scanning electron microscopy (SEM), weight loss, adsorption isotherm, surface roughness, and DFT calculations, and the corresponding Raman spectra are displayed in Figure 7, as Q235 steel immersed in 1 M HCl solution without FH inhibitor, the characteristic peaks around 1320, 674, and 550 cm −1 are related to the α‐Fe 2 O 3 , β‐FeOOH, and Fe 3 O 4. 43–45 Furthermore, in the presence of FH inhibitors, the sharp peak of steel at 2329 cm −1 appears in HCl medium, which should be attributed to the uneven corrosion of iron. The existence of these clear peaks confirms the existence of iron oxide, indicating the formation of corrosion products.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the electrochemical results, the similar electrochemical behaviors at 298 and 308 K are observed for the corrosion inhibition performance of Q235 steel as incorporation of FH inhibitor; thus, the electrochemical test results of Q235 steel at 298 K are selected to conduct the subsequent characterizations, such as Raman, scanning electron microscopy (SEM), weight loss, adsorption isotherm, surface roughness, and DFT calculations, and the corresponding Raman spectra are displayed in Figure 7, as Q235 steel immersed in 1 M HCl solution without FH inhibitor, the characteristic peaks around 1320, 674, and 550 cm −1 are related to the α‐Fe 2 O 3 , β‐FeOOH, and Fe 3 O 4. 43–45 Furthermore, in the presence of FH inhibitors, the sharp peak of steel at 2329 cm −1 appears in HCl medium, which should be attributed to the uneven corrosion of iron. The existence of these clear peaks confirms the existence of iron oxide, indicating the formation of corrosion products.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of methionine as a corrosion inhibitor investigated by Lai et al on twinning induced plastic steel in 3.5 wt.% NaCl solutions. 17 With the increase of inhibitor concentration, the corrosion inhibition rate first increased and then decreased. The maximum inhibition efficiency was about 30 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Phenylalanine shows 89% inhibition efficiency, more than leucine and valine. The effect of methionine as a corrosion inhibitor investigated by Lai et al on twinning induced plastic steel in 3.5 wt.% NaCl solutions 17 . With the increase of inhibitor concentration, the corrosion inhibition rate first increased and then decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported [15][16][17][18][19][20][21][22] that organic compounds can act as powerful corrosion inhibitors for numerous metals and alloys in various corrosive media. Particularly, those compounds with polar groups that include N, O, and S and double bonds are excellent corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this adsorption is affected by the number of points such as the charge of the surface of metal, its nature, the mode of adsorption, the structure of the inhibitor, and finally the corrosiveness of the medium [18]. Several compounds with these characteristics have been reported to be efficient corrosion inhibitors for iron in corrosive media; for example, 3-amino-5-mercapto-1,2,4-triazole [1], benzotriazole [2], 5-(3-aminophenyl)-tetrazole [3], 1,1'-thiocarbonyldiimidazole [5], amino acids [7], monoalkyl phosphate esters [19], methionine [21], and cetylpyridinium chloride [22], etc.…”
Section: Introductionmentioning
confidence: 99%